An investigation into the usage of information technology in quantity surveying firms in the Klang Valley - Raden Sugijanto, Raden Iman Darmawan (2000)
The rapid and pervasive growth of IT has prompted organisations to consider the role of IT in supporting their business processes. So what is IT and how does the Quantity Surveyors use IT? As information is the lively-hood of the quantity surveying professions, by having the right IT facilities it should benefit their profession. The Malaysian Quantity Surveying firms have realised that the effective use of IT provides competitive edge. But how many of the Quantity Surveying firms have been using IT and how effective have they utilised their IT facilities? The objective ot this research is to identify the uses of IT in quantity surveying firms. It highlights how IT is adopted and used to help the quantity surveyor's tasks and objectives. The research also look at some of the problems encountered and the benefits gained when implementing IT.